Помогите пожалуйста решить уравнение (х-2)(х-3)-х(х+4)+7=х+5

0 голосов
36 просмотров

Помогите пожалуйста решить уравнение (х-2)(х-3)-х(х+4)+7=х+5


Алгебра (100 баллов) | 36 просмотров
Дан 1 ответ
0 голосов
Правильный ответ
(х - 2)(х - 3) - х(х + 4) + 7 = х + 5
х
² - 3х - 2х + 6 - х² - 4х + 7 = х + 5
-9х + 13 = х + 5
-9х - х = 5 - 13
-10х = -8
х = 0,8
(51.1k баллов)
0

Спасибо

0

(х - 2)(х - 3) - х(х + 4) + 7 = х + 5
х² - 3х - 2х + 6 - х² - 4х + 7= х + 5
-9х + 6 + 7 = х + 5
-9х - х = 5 - 13
-10х = -8
х = 0,8
Проверка
(0,8 - 2)(0,8 - 3) – 0,8*(0,8 + 4) + 7 = 0,8 + 5
1,2 * 2,2 – 3,84 + 7 = 5,8
5,8 = 5,8
Ответ: 0,8

0

Спасибо.